What Is New in Genetics of Congenital Heart Defects? - Digilio, Maria Cristina; Marino, Bruno (Frontiers in Pediatrics, 2016)
Epidemiological studies, clinical observations and advances in molecular genetics are contributing to the understanding of the etiology of congenital heart defects (CHDs). Several phenotype-genotype correlation studies have suggested that specific morphogenetic mechanisms put in motion by genes can result in a specific cardiac phenotype. The use of new technologies has increased the possibility of identification of new genes and chromosomal loci in syndromic and non-syndromic CHDs. There are a number of methods available for genetic research studies of CHDs, including cytogenetic analysis, linkage and association studies, copy number variation (CNV) and DNA micro-array analysis, and whole exome sequencing. The altered dosage of contigous genes included inside CNVs can produce new syndromic CHDs, so that several different new genomic conditions have been identified. These include duplication 22q11.2 syndrome, distal 22q11.2 deletion syndrome, deletion and duplication 1q21.1, deletion 1p36 syndrome. Molecular techniques as whole exome sequancing has lead to the identification of new genes for monogenic syndromes with CHD, as for example in Adams-Oliver, Noonan and Kabuki syndrome. The variable expressivity and reduced penetrance of CHDs in genetic syndromes is likely influenced by genetic factors, and several studies have been performed showing the involvement of modifier genes. It is not easy to define precisely the genetic defects underlying non-syndromic CHDs, due to the genetic and clinical heterogeneity of these malformations. Recent experimental studies have identified multiple CNVs contributing to non-syndromic CHD. The number of identified genes for non-syndromic CHDs is at this time limited and each of the identified gene has been shown to be implicated only in a small proportion of CHD. The application of new technologies to specific cases of CHD and pedigrees with familial recurrence and filtering genes mapping in CNV regions can probably in the future add knowledges about new genes for non-syndromic CHDs.